Cultural Values In The Novel "The Legend Of Condor Heroes" (Shen Diao Xia Lü) From Jin Yong - Luo Ying (IJLECR (International Journal of Language Education and Cultural Review), 2016)
The purpose of this research is to understand deeply about cultural values in the novel "The legend of Condor Heroes" from Jin Yong. This research uses qualitative method with structural semiotic approach. The results of this research showed the theme from this novel was about love, plot were progressive and dramatic, setting was in Dynasty of Zhong, and the point of view used third person. There were also found cultural values from semiotic aspects from Icon, indeks, and symbol they were independent, zhi (wise), control of emotion, Li (morality), Lian (pure heart), Ren (affection), Zhong (loyal), simplicity, Xiao (obedient), interflow with nature, accomplishing character, Yi (responsibility), praying, and obey rules of Budha.